2016
DOI: 10.1113/jp270678
|View full text |Cite
|
Sign up to set email alerts
|

Rescuing cardiac automaticity in L‐type Cav1.3 channelopathies and beyond

Abstract: Pacemaker activity of the sino-atrial node generates the heart rate. Disease of the sinus node and impairment of atrioventricular conduction induce an excessively low ventricular rate (bradycardia), which cannot meet the needs of the organism. Bradycardia accounts for about half of the total workload of clinical cardiologists. The 'sick sinus' syndrome (SSS) is characterized by sinus bradycardia and periods of intermittent atrial fibrillation. Several genetic or acquired risk factors or pathologies can lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 62 publications
1
18
0
1
Order By: Relevance
“… 22 , 23 , 29 Indeed, as previously reported Ca V 1.3 constitutes the major L-type Ca 2+ channel isoform in the diastolic depolarization of the mouse SAN AP and in support of this observation, previous studies have shown that deletion of Ca V 1.3 resulted in bradycardia and dysrhythmic SAN pacemaking. Furthermore, Ca V 1.3 was demonstrated to play a critical role in modulating intra-cellular Ca 2+ dynamics by regulating Ca 2+ release from the SR. 22 , 23 , 29 Although it was shown that Ca V 1.3 deletion resulted in an inhibition of Ca 2+ transients, it is very likely that the increase in Ca V 1.3 we observed here, along with the increase in RyR2, serves the opposite purpose: increasing Ca 2+ transient rate and robustness of the Ca V 1.3/RyR2 coupling, thereby sustaining the elevated HR during pregnancy. In support of this notion, Torrente et al 22 recently reported that Ca V 1.3 channels co-localize with RyR2 in mouse SAN cells, which would favour the Ca 2+ -induced Ca 2+ release from the SR.…”
Section: Discussionsupporting
confidence: 70%
“… 22 , 23 , 29 Indeed, as previously reported Ca V 1.3 constitutes the major L-type Ca 2+ channel isoform in the diastolic depolarization of the mouse SAN AP and in support of this observation, previous studies have shown that deletion of Ca V 1.3 resulted in bradycardia and dysrhythmic SAN pacemaking. Furthermore, Ca V 1.3 was demonstrated to play a critical role in modulating intra-cellular Ca 2+ dynamics by regulating Ca 2+ release from the SR. 22 , 23 , 29 Although it was shown that Ca V 1.3 deletion resulted in an inhibition of Ca 2+ transients, it is very likely that the increase in Ca V 1.3 we observed here, along with the increase in RyR2, serves the opposite purpose: increasing Ca 2+ transient rate and robustness of the Ca V 1.3/RyR2 coupling, thereby sustaining the elevated HR during pregnancy. In support of this notion, Torrente et al 22 recently reported that Ca V 1.3 channels co-localize with RyR2 in mouse SAN cells, which would favour the Ca 2+ -induced Ca 2+ release from the SR.…”
Section: Discussionsupporting
confidence: 70%
“…We have chosen mice (Mus musculus) as the model animal species for this study. Mice were considered for our experiments, because of the availability in our laboratory of genetically modified strains recapitulating congenital primary SND 53 . To the best of our knowledge, no alternative animal models of primary SND are available.…”
Section: Methodsmentioning
confidence: 99%
“…Comme indiqué dans les paragraphes précédents, la perte de fonction des canaux f-HCN4 et Ca v 1.3 induit des dysfonctions sinusales chez les souris génétiquement modifiées et chez l’homme. Nous avons montré que l’ablation génétique ou l’inhibition pharmacologique des canaux Girk4 codant pour I KACh normalise la fréquence et le rythme cardiaque des souris Ca v 1.3 −/− et HCN4-AYA [5,14]. Nos résultats montrent que la normalisation de la fonction sinu-sale et l’amélioration de la conduction s’expliquent par un phénomène de rétablissement de l’équilibre entre courants entrants et sortants activés dans la dépolarisation diastolique (Fig.…”
Section: Le Ciblage Du « Canal Compensatoire » : Une Nouvelle Perspecunclassified